Pemberdayaan Remaja Putus Sekolah Di Panti Sosial Bina Remaja Majar Tabela Kota Palangka Raya - Irwani Irwani; Joko Prasetio (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
The purpose of this research is to know and describe the empowerment of dropouts youth in the Youth Community Development (PSBR) of Palangka Raya City. Given the empowerment of school, dropouts is an effort to improve the dignity of the community and to be in poor condition, so that they can escape the pitfalls of poverty and retardation. Therefore, service through the social orphanage system is essentially a preventive, healing, rehabilitation and development of the potential of dropouts. Methods of research using qualitative dendritic research. The data collection techniques used in this study were observations, interviews, and documentation. While the analytical techniques used are qualitative descriptive analysis. The results showed that the form of empowerment carried out in 4 (four) forms of (1) physical guidance, (2) Mental guidance, (3) social guidance, and (4) guidance of recommended skills: (1) continuing to socialize, (2) Add to the type of Skills guidance, (3) improving means and infrastructure, (4) Increasing motivation for clients, (5) Improving self-discipline, and (6) digging into their abilities and potential.